Uncovering the differences among displaced workers: Evidence from Canadian job separation records - Serdar Birinci; Youngmin Park; Thomas Pugh; Kurt See (Bank of Canada, 2023)
We revisit the measurement of the sources and consequences of job displacement using Canadian job separation records. To circumvent administrative data limitations, conventional approaches address selection by identifying displacement effects through mass-layoff separations, which are interpreted as involuntary. We refine this procedure and find that only a quarter of mass-layoff separations are indeed layoffs. Isolating mass-layoff separations that reflect involuntary displacement, we find twice the earnings losses relative to existing estimates. We uncover heterogeneity in losses for separations with different reasons and timing, ranging from 15 percent for quits after a mass layoff to 60 percent for layoffs before it.
Keywords: E24; E32; J31; J63; J65; 330; Labour markets; Potential output; Productivity